PENGARUH PENAMBAHAN BAHAN FOAM AGENT DENGAN VARIASI KOMPOSISI BATU KAPUR TERHADAP KUAT TEKAN BATA RINGAN - Ahmad Syapawi Syapawi; Kosim Kosim; Ricky Ravsyan; Andriani Effendi; Fitri Apriani (PILAR, 2022)
This research was conducted to determine the effect of limestone substitution on cement on the value of compressive strength and weight of the contents of cellular lightweight concrete (CLC). The method used in this study is to make CLC light brick with limestone substitution as much as 0%, 5%, 10%, and 15% of cement weight. The light bricks that have been curing for 7, 14 and 28 days are then tested to obtain for compressive strength value and weight of the contents of the light brick.The results showed the value of compressive strength CLC light brick 7 days age was 2.0 Mpa, with limestone substitution as much as 5 %, 10 %, and 15 % respectively was 2.2 MPa 2.3 MPa and 4.3 MPa. The normal CLC light brick compressive strength at 14 days of age is 2.6 Mpa, with limestone substitutions of 5%, 10%, and 15% respectively at 3.2 MPa of 3.1 MPa and 4.6 MPa. While the normal CLC light brick compressive strength at 28 days age is 3.3 Mpa, with limestone substitutions of 5 %, 10%, and 15% respectively is 3.3 MPa 3.6 MPa and 5.7 MPa. Furthermore, in the test of light brick content weight age 28 days with successive limestone substitution of 0%, 5%, 10% and 15% obtained results of 867.6 Kg/m3, 1201.6 Kg/m3, 1110.1 Kg/m3, and 1426.1 Kg/m3The minimum compressive strength standard of light brick is 1-15 MPa and the standard of medium strength light brick is 800-1320 Kg/m3 therefore it can be concluded that the light brick that we researched has met the standards and can be used in the manufacture of light bricks on commercial use